Assessment of Pesticide Use, Practice and Risk in Gedeo and Borena Zones; Ethiopia - Tilahun, Beniam; Hussen, Ahmed (International Journal of Environment, 2014)
This research attempts to assess pesticide use, practice and risk in Gedeo and Borena Zones. Three sample districts have been selected purposively from these zones and four sub districts from each district. Primary data was collected through in depth interview and group discussion. Results show that people in the sample area use pesticides for crop production and ectoparasites. Malathion, DDT, Karate and 2-4D are chemicals frequently used to control pests. Majority of the respondents used these pesticides by their own decision for the intended purpose and purchase pesticides from private shops, local market and government offices. Farmers mostly spray by themselves; however all of them spray pesticides without proper protection. Pesticide containers are usually thrown anywhere after use and in some cases used for home consumption. All of the respondents took no training about pesticide use, many do not read labels including expiry date when they buy or use pesticides and doesn’t know recommended dose for application. There were pesticide poisoning incidents recorded such as poisoned-recovered, illness/injury and death incidents; mainly due to poor storage, careless disposal, unsafe application and suicidal behaviour. It can be concluded that there is a wrong pesticide use and practice in the sample area and risk is observed to be high. Universally prohibited pesticides like DDT were found in use for crop production and household pests. Therefore, proper training and awareness has to be created to the community. Moreover, government bodies should regularly educate as well as monitor, control and regulate pesticide trade, use and practice in the area. DOI: http://dx.doi.org/10.3126/ije.v3i3.11079 International Journal of Environment Vol.3(3) 2014: 201-209